The Effects of Incorporating Non-linearity in LCA: Characterizing the Impact on Human Health - Li, Dingsheng; Tao, Mengya; Vieira, Jessica; Suh, Sangwon (Frontiers in Sustainability, 2020)
Processes that govern environmental mechanisms including fate, transport, and exposure are generally non-linear. Characterization models in life cycle impact assessment (LCIA), however, often linearize such processes, while the implications of linearizing non-linear processes have not been fully understood. Recently, non-linear models have been incorporated into characterization modeling, allowing the opportunity for a comparison. Here, we test potential effects of incorporating three types of non-linear processes into life cycle assessment (LCA): emission rate, environmental fate, and exposure-response. We compare the characterized results of human health impact due to non-cancer effects using (1) USEtox, a conventional, steady-state model and (2) the CLiCC suite, which employs dynamic emissions profiles, non-steady state fate and transport, and no-effect exposure thresholds. Under constant emission rates, the two approaches display comparable results over a long period of time. When significant temporal variations are introduced to emission rates, however, the results from the two approaches start to deviate. On the one hand, pulse emissions averaged over time tend to show lower human health impacts under USEtox as compared to CLiCC suite, as the level of exposure shortly after the pulse emission temporarily shifts the dose-response regime to a steeper territory in the curve. On the other hand, USEtox, in the absence of no-effect exposure thresholds, tends to show higher human health impacts compared to CLiCC suite for low-level emissions with little temporal variation. Our results call for a careful interpretation of characterized results, especially when the emissions are known to exhibit large temporal variations.